Prehospital Management of Sepsis: Early Identification and Intervention (The Review of Diabetic Studies, 2025)
Sepsis remains a leading cause of morbidity and mortality worldwide, with timely recognition and intervention being critical to survival. In the prehospital setting, paramedics are uniquely positioned to initiate early sepsis care, yet challenges in diagnosis, training, and standardized protocols persist. This review synthesizes current evidence on the role of paramedics in early sepsis identification and intervention. Screening tools such as qSOFA, NEWS2, and PRESS offer varying sensitivity and specificity, while clinical gestalt and real-time telemedicine support can complement structured scoring systems. Key prehospital interventions include fluid resuscitation, oxygen therapy, airway management, point-of-care lactate testing, and, in some systems, early antibiotic administration. Prehospital alerts and structured handover systems enhance continuity of care, reducing delays in hospital-based sepsis bundles. Despite promising evidence that early prehospital interventions improve time-to-treatment and outcomes, barriers such as diagnostic uncertainty, limited protocols, and regulatory restrictions remain. Future directions include integration of artificial intelligence, advanced point-of-care diagnostics, expanded paramedic scope of practice, and rigorous multicenter research to standardize and optimize care. Strengthening prehospital sepsis management has the potential to reduce mortality, improve patient outcomes, and alleviate healthcare system burdens.